People of the Deer - Mowat, Farley (Carroll & Graf, 2005)
In 1886, the Ihalmiut people of northern Canada numbered seven thousand; by 1946, when Farley Mowat began his two-year stay in the Arctic, the population had fallen to just forty. With them, he observed for the first time the phenomenon that would inspire him for the rest of his life: the millennia-old migration of the Arctic's caribou herds. He also endured bleak, interminable winters, suffered agonizing shortages of food, and witnessed the continual, devastating intrusions of outsiders bent on exploitation. Here, in this classic and first book to demonstrate the mammoth literary talent that would produce some of the most memorable books of the next half-century, best-selling author Farley Mowat chronicles his harrowing experiences. People of the Deer is the lyrical ethnography of a beautiful and endangered society. It is a mournful reproach to those who would manipulate and destroy indigenous cultures throughout the world. Most of all, it is a tribute to the last People of the Deer, the diminished Ihalmiuts, whose calamitous encounter with our civilization resulted in their unnecessary demise.